Rozwiązywanie zadań tekstowych przez studentów – przyszłych nauczycieli edukacji wczesnoszkolnej - Beata Bugajska-Jaszczołt; Monika Czajkowska (Problemy Wczesnej Edukacji)
The results of the research aimed at diagnosing the ability to solve textual tasks by the students – candidates for lower primary teachers are presented in the article. The research was carried out between the years 2017 and 2019. It comprised 392 students of pedagogy with teaching specialization. The main research method was a competency test, and the technique was document analysis. The research shows that the students have well-mastered calculational algorithms and techniques but they have difficulties in presenting their reasoning in the language of mathematics. A large group of students strive to write down the solution in the form of a ready mathematical formula, without representing the situation on a drawing/diagram or manipulating on concretes to help them solve the problem.